Designing of specimen shape for biaxial stretching experiments - Mokhireva, Ksenia Aleksandrovna; Svistkov, Aleksandr Lvovich; Shadrin, Vladimir Vasilievich (Computational Continuum Mechanics, 2014)
In-plane biaxial stretching of cruciform specimens made of elastomeric materials is considered. This type of experiments provides additional information about the properties of materials with complex mechanical behavior. However, due to large deformations and a high degree of distortion peculiar to elastomers, an inhomogeneous strain field and, consequently, a nonuniform stress field are generated across the central part (working area) of the specimen. To achieve uniform loading of the central part of the specimen, some changes of the initial specimen geometry (number and size of arm strips transferring loads to the central part of the specimen and others) should be done. A numerical analysis of the effect of a cruciform specimen shape on the uniformity of the stress-strain fields in the working area of the specimen has been performed using the ABAQUS Finite Element Analysis (FEA) software. The problem of nonlinear elasticity is solved numerically, and the behavior of elastomeric material is described by the neo-Hookean, Mooney-Rivlin and Arruda-Boyce strain energy potentials. Based on the comparison of the obtained results, we have chosen an optimal shape of the cruciform specimen for biaxial testing, which allows us to achieve the maximum uniform stress-strain state in the area of interest. In the modified version, the specimen arm strips are transformed into the fan-shaped strips while fixing in the testing machine grips. The efficiency of the proposed specimen shape has been validated by experiments involving a visual inspection of the uniformity of strain field in the specimens made of materials with the softening effect and viscoelastic properties.